2018
DOI: 10.3390/ph11020050
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-Deactivation CB1 Receptor Ligands as a Novel Strategy to Lower Intraocular Pressure

Abstract: Nearly half a century has passed since the demonstration that cannabis and its chief psychoactive component Δ9-THC lowers intraocular pressure (IOP). Elevated IOP remains the chief hallmark and therapeutic target for glaucoma, a condition that places millions at risk of blindness. It is likely that Δ9-THC exerts much of its IOP-lowering effects via the activation of CB1 cannabinoid receptors. However, the initial promise of CB1 as a target for treating glaucoma has not thus far translated into a credible thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…For instance, we have shown that it is possible to enhance endogenous cannabinoid signaling by blocking the cannabinoid-metabolizing enzyme monoacylglycerol lipase 37 and so lower ocular pressure. Similarly, we have found that activating CB1 directly 38 can achieve the same outcome. Our findings for THC suggest that a dual CB1/GPR18 agonist may prove advantageous.…”
Section: Discussionsupporting
confidence: 73%
“…For instance, we have shown that it is possible to enhance endogenous cannabinoid signaling by blocking the cannabinoid-metabolizing enzyme monoacylglycerol lipase 37 and so lower ocular pressure. Similarly, we have found that activating CB1 directly 38 can achieve the same outcome. Our findings for THC suggest that a dual CB1/GPR18 agonist may prove advantageous.…”
Section: Discussionsupporting
confidence: 73%
“…28,29 In addition, non-psychotropic cannabinoids and other CB1 receptor targets are being investigated for potential treatments that avoid systemic effects. 30,31 There are several limitations to this study. First, the number of subjects in the placebo group was small and may have introduced error into the results from the natural variability in IOP during the diurnal period.…”
Section: Touchreviews In Ophthalmologymentioning
confidence: 97%
“…However, novel compounds with improved corneal penetration are being developed for topical administration, thereby mitigating systemic side-effects (10)(11)(12)(13)(14)34). Non-psychotropic cannabinoids and other CB1 receptor targets are being investigated for potential treatments that avoid systemic effects (35,36). In addition, formulations are being developed to improve duration of action (37).…”
Section: Data Availability Statementmentioning
confidence: 99%